The Response of two Wheat Cultivars Triticumspp to Cytokinin and Water Stress Treatments and their Interactions - Sakri, Faisal- Abdlkadir; Amin, Shireen- AbdulKerim (Sulaimani Journal for Pure and Applied Sciences, 2009)
This research had been conducted to investigate the response of two wheat cultivars to cytokinin and droughtness treatments through plant height, number of tillers per plant, flag leaf length, number of kernel per spike, weight of 100 kernels, protein, and total carbohydrates content of kernels. The maximum mean value for plant height was recorded for Sham-3 cultivar at 80 ppm which is significantly increased as compare to control, while the flag leaf length increased nonsignificantly at 40 ppm. Treatments with 40 and 80 ppm significantly decrease weight of 100 kernels for Mexipak cultivar, while in Sham-3 cytokinin at all concentrations significantly decreased weight of 100 kernels. It is obvious that cytokinin treatments with drought plants was less affective compared with normal irrigation with regard to carbohydrate content for Mexipak cultivars. In Sham-3, the results showed that the carbohydrate percentage in all cytokinin treated plants whether, drought or irrigated, were decreased significantly, while the weight of 100 kernels has not been changed in CK3D compare to the CK0N but increased significantly when compared with CK0D.
Keywords: Various wheat Triticum aestivum L; Triticum durum L; cytokinin; waterstress